Ceramic sintered body, and plasma generation electrode
A ceramic sintered body with a specific elemental composition and single-phase structure addresses oxidation issues, enhancing durability and lifespan in plasma generation electrodes.
Patent Information
- Application Number
- JP2023110100
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2043-07-04
AI Technical Summary
Existing ceramic sintered bodies used for plasma generation electrodes lack sufficient oxidation resistance, leading to reduced lifespan and increased wear due to oxidation and melting under plasma conditions.
A ceramic sintered body composed of specific elements such as titanium, zirconium, niobium, molybdenum, hafnium, tantalum, and tungsten, with a single-phase structure and controlled carbon and iron concentrations, enhancing oxidation resistance and wear resistance.
The ceramic sintered body exhibits improved oxidation resistance and extended lifespan by suppressing oxidation and melting, allowing for a more durable plasma generation electrode with reduced manufacturing costs.
Smart Images

Figure 2025008162000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a ceramic sintered body and an electrode for generating plasma. [Background technology]
[0002] 2. Description of the Related Art Conventionally, ceramic sintered bodies used for electrodes for generating plasma have been known (for example, Patent Document 1 and Non-Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6929755 [Non-patent literature]
[0004] [Non-Patent Document 1] Shiro Shimada, Michio Inagaki, Kunihito Matsui, "Oxidation Kinetics of Hafnium Carbide in the Temperature Range of 480° to 600°C", Journal of the American Ceramic Society, Volume 75, Issue 10, October 1992, Pages 2671-2678, [Retrieved May 9, 2023], Internet<https: / / doi.org / 10.1111 / j.1151-2916.1992.tb05487.x> Summary of the Invention [Problem to be solved by the invention]
[0005] However, even with the prior art such as Patent Document 1 and Non-Patent Document 1, there is still room for improvement in the technology for improving the oxidation resistance of a ceramic sintered body.
[0006] An object of the present invention is to provide a technique for improving the oxidation resistance of a ceramic sintered body. [Means for solving the problem]
[0007] The present invention has been made to solve at least part of the above-mentioned problems, and can be realized in the following forms.
[0008] (1) According to one embodiment of the present invention, a ceramic sintered body is provided, which includes a first specific element consisting of five or six elements selected from titanium (Ti), vanadium (V), zirconium (Zr), niobium (Nb), molybdenum (Mo), hafnium (Hf), tantalum (Ta), and tungsten (W), a second specific element consisting of one element selected from yttrium (Y) and aluminum (Al), and a carbon element (C), the total of the first specific element, the second specific element, and the carbon element contained in the ceramic sintered body is 98 at% or more, the second specific element contained in the ceramic sintered body is 3000 atppm or less, the carbon contained in the ceramic sintered body is 45 at% or more and 55 at% or less, and has a single-phase structure in which the first specific element is dissolved.
[0009] According to this configuration, the ceramic sintered body has a single-phase structure in which the first specific elements consisting of five or six elements selected from titanium, vanadium, zirconium, niobium, molybdenum, hafnium, tantalum, and tungsten are dissolved in a solid solution, thereby improving the oxidation resistance of the ceramic sintered body.
[0010] (2) In the ceramic sintered body of the above embodiment, the first specific element may include zirconium. According to this configuration, the ceramic sintered body includes zirconium as the first specific element, which has a larger ionic radius than any of titanium, vanadium, niobium, molybdenum, hafnium, tantalum, and tungsten. This increases the distortion of the crystal lattice in the single-phase structure in which the first specific element is dissolved. Therefore, the ceramic sintered body is less susceptible to oxidation, and the oxidation resistance of the ceramic sintered body can be further improved.
[0011] (3) In the ceramic sintered body of the above embodiment, the iron element (Fe) contained in the ceramic sintered body may be 800 atppm or less. According to this configuration, since the concentration of the iron element in the ceramic sintered body is 800 atppm or less, the precipitation of iron-based particles is suppressed. As a result, melting of the ceramic sintered body due to a rise in temperature is suppressed, and the weight loss of the ceramic sintered body due to use can be suppressed.
[0012] (4) According to another aspect of the present invention, there is provided an electrode for plasma generation. This electrode for plasma generation includes the ceramic sintered body of the above aspect. According to this configuration, since the electrode for plasma generation includes the ceramic sintered body having a single-phase structure in which the first specific element is dissolved, the oxidation resistance of the electrode for plasma generation can be improved. This can extend the life of the electrode for plasma generation.
[0013] The present invention can be realized in various aspects, for example, in the form of a method for manufacturing a ceramic sintered body, an apparatus including a ceramic sintered body, a method for controlling an apparatus including a ceramic sintered body, etc. [Brief description of the drawings]
[0014] [Figure 1] 1 is a cross-sectional view of a plasma generation electrode including a ceramic sintered body according to a first embodiment. [Diagram 2] FIG. 1 is a first diagram for explaining the preparation conditions for samples of sintered ceramic bodies. [Diagram 3] FIG. 2 is a second diagram for explaining the preparation conditions for the ceramic sintered body samples. [Figure 4] FIG. 1 is a first diagram illustrating the characteristics of a sample of a ceramic sintered body. [Diagram 5] FIG. 2 is a second diagram illustrating the characteristics of the sample of the ceramic sintered body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] First Embodiment 1 is a cross-sectional view of a plasma generation electrode 10 including an electrode tip 1 (ceramic sintered body) of this embodiment. The plasma generation electrode 10 of this embodiment is used to generate, for example, oxygen plasma in a cutting machine, a surface treatment device, a thermal spraying device, etc. that uses plasma. The plasma generation electrode 10 includes the electrode tip 1 as a plasma generation cathode and a tip support part 2 that supports the electrode tip 1.
[0016] The electrode tip 1 is a ceramic sintered body, and contains a first specific element consisting of five or six elements selected from titanium (Ti), vanadium (V), zirconium (Zr), niobium (Nb), molybdenum (Mo), hafnium (Hf), tantalum (Ta), and tungsten (W), a second specific element consisting of one element selected from yttrium (Y) and aluminum (Al), and a carbon element (C). The total of the first specific element, the second specific element, and the carbon element contained in the electrode tip 1 is 98 at% or more, and the second specific element is 3000 atppm or less. The total of the first specific element, the second specific element, and the carbon element may be 100 at%, and the second specific element may be 0 atppm. The carbon contained in the electrode tip 1 is 45 at% or more and 55 at% or less. The concentration of the first specific element and the concentration of carbon element in the electrode tip 1 are measured by using energy dispersive X-ray spectroscopy (EDS). The identification and concentration measurement of the second specific element in the electrode tip 1 are performed by using an inductively coupled plasma (ICP) optical emission spectrometer.
[0017] The electrode tip 1 of this embodiment has a single-phase structure in which the first specific element is dissolved. In this embodiment, whether the electrode tip 1 has a single-phase structure in which the first specific element is dissolved is identified by X-ray diffraction using an X-ray diffraction device. Specifically, in an analysis of the crystal structure of the electrode tip 1 by X-ray diffraction using CuKα1 radiation, when 2θ is measured from 20° to 80°, a NaCl type structure is identified. <111> direction, <200> direction, <220> direction, <311> direction, <222> When only one peak originating from each of the directions is present in each of the ranges of 30.0° to 37.2°, 34.8° to 43.1°, 50.2° to 62.3°, 59.7° to 74.4°, and 62.7° to 78.5°, the electrode tip 1 is judged to have a single-phase structure. When two or three peaks are observed in any of the ranges of 30.0° to 37.2°, 34.8° to 43.1°, 50.2° to 62.3°, 59.7° to 74.4°, and 62.7° to 78.5°, the electrode tip 1 is judged to have a multi-phase structure.
[0018] The electrode tip 1 of this embodiment contains five types of elements, titanium, zirconium, niobium, hafnium, and tantalum, as the first specific element. The electrode tip 1 preferably contains a combination of titanium, zirconium, hafnium, and tantalum as the combination of the first specific element. The electrode tip 1 preferably contains zirconium and hafnium as the combination of the first specific element, more preferably contains zirconium, hafnium, and tantalum, and further preferably contains zirconium, hafnium, tantalum, and titanium. The electrode tip 1 has a zirconium element concentration of 8.43 at% and is not easily oxidized in an atmosphere containing oxygen plasma. The ceramic sintered body provided in the electrode tip 1 contains yttrium as the second specific element.
[0019] The electrode tip 1 of this embodiment contains iron element as an inevitable impurity. In this embodiment, the iron element (Fe) contained in the electrode tip 1 is 800 atppm or less. The iron element in the electrode tip 1 may be 0 atppm.
[0020] The electrode tip 1 of this embodiment has a single-phase structure in which the first specific element is dissolved, and is therefore a relatively dense ceramic sintered body with few pores. The density of the ceramic sintered body is expressed by the magnitude of the relative density calculated using the theoretical density value calculated from the lattice constant obtained by Rietveld analysis and the specific gravity and open porosity measured by the method according to JIS R1634. The electrode tip 1 of this embodiment has a relative density of more than 97%.
[0021] In the electrode tip 1 of this embodiment, the concentration difference between the first specific elements is less than 5 at%, so that a single-phase structure of solid solution is easily formed. In this embodiment, the concentration difference between the first specific elements is obtained from the calculation result of the composition ratio in the crystal grains using energy dispersive X-ray spectroscopy.
[0022] The tip support 2 is a cylindrical member with a bottom, and is formed, for example, by processing a rod-shaped member made of copper. A hole 2b into which the electrode tip 1 is fitted is formed in the bottom 2a of the tip support 2. The plasma generation electrode 10 of this embodiment is completed when the electrode tip 1 is fitted into the hole 2b of the tip support 2.
[0023] Next, a manufacturing method of the electrode chip 1 will be described. As a manufacturing method of the electrode chip 1, first, weighed metal powder is put into a ball mill together with ethanol, and mixed and pulverized for 20 hours to prepare a metal powder mixture. The types of metal powder to be weighed are titanium carbide powder (average particle size: 1.7 μm), zirconium carbide powder (average particle size: 2.4 μm), niobium carbide powder (average particle size: 1.1 μm), hafnium carbide powder (average particle size: 0.7 μm), and tantalum carbide powder (average particle size: 1.0 μm), and each is weighed to be 20 mol% in the prepared metal powder mixture. Next, zirconium partially stabilized with 3 mol% yttria (Y2O3) (hereinafter referred to as "3YSZ") is added to the prepared metal powder mixture in an amount equivalent to 0.4 wt% of the prepared metal powder mixture, and further mixed and pulverized for 20 hours to prepare a slurry. The prepared slurry is dried in a hot water bath to prepare a dry powder. The dried powder thus produced is passed through a sieve with 100 μm openings to obtain granulated powder, which is then placed in a mold for hot pressing and sintered at a pressure of 30 MPa in a vacuum atmosphere at a temperature of 1900° C., to complete the electrode chip 1.
[0024] Next, an evaluation test for a ceramic sintered body used as an electrode tip of an electrode for generating plasma will be described. In this evaluation test, a number of ceramic sintered bodies were produced under different production conditions, and the effects of the production conditions on the properties of the ceramic sintered bodies were evaluated.
[0025] FIG. 2 is a first diagram for explaining the preparation conditions of the ceramic sintered body samples. FIG. 3 is a second diagram for explaining the preparation conditions of the ceramic sintered body samples. In this evaluation test, 29 types of samples 1 to 29 were prepared as ceramic sintered body samples. FIG. 2 and FIG. 3 show the preparation conditions of each of the samples 1 to 29, such as the type and mole percentage of the "main raw material," the type and weight percentage of the "additive," and the "firing method," "temperature" (unit: °C), and "pressure" (unit: MPa) as the "firing conditions."
[0026] First, the "main raw material" which is the first specific element contained in the ceramic sintered body will be described. In the preparation of Samples 1 to 29, Samples 1 to 21 and 24 to 29, one to eight types of materials from titanium carbide, vanadium carbide, zirconium carbide, niobium carbide, molybdenum carbide, hafnium carbide, tantalum carbide, and tungsten carbide were used as the "main raw material" as shown in Figures 2 and 3. In the preparation of Samples 1 to 21 and 24 to 29, powders of the "main raw material" having the average particle diameters shown below were used. Titanium carbide powder: 1.7μm Vanadium carbide powder: 1.8μm Zirconium carbide powder: 2.4μm Niobium carbide powder: 1.1μm Molybdenum carbide powder: 1.8μm Hafnium carbide powder: 0.7μm Tantalum carbide powder: 1.0μm Tungsten carbide powder: 1.1μm
[0027] Next, the "additive" that is the second specific element contained in the ceramic sintered body will be described. In the preparation of Samples 1 to 21, 25 to 29, either 3YSZ or aluminum oxide (Al2O3) was used as the "additive" as shown in Figs. 2 and 3. In the preparation of Samples 1 to 21, 24 to 29, powder of the "additive" having the average particle size shown below was used. In Sample 24, 0.4 wt% of zirconia (ZrO2) was used as the "additive". Details of the raw materials used in the preparation of Samples 22 and 23 will be described later. 3YSZ: 1.0 μm Al2O3: 0.3μm
[0028] In the preparation of samples 1 to 21 and 24 to 29, a metal powder mixture was prepared in the same manner as in the preparation of the electrode tip 1. In the preparation of the metal powder mixture, the "main raw material" in the metal powder mixture was weighed out so that the molar percentage was the numerical value shown in FIG. 2 or FIG. 3, and the mixture was put into a ball mill together with ethanol, and mixed and crushed for 20 hours. In sample 25, equal amounts of titanium carbide, vanadium carbide, and niobium carbide were weighed out so that the total of the main raw materials was approximately 100 mol%, and the mixture was put into a ball mill together with ethanol, and mixed and crushed for 20 hours. In samples 1 to 21 and 25 to 29, the "additive" was added in an amount corresponding to the numerical value shown in FIG. 2 or FIG. 3 relative to the weight of the prepared metal powder mixture, and further mixed and crushed for 20 hours to prepare a slurry. In sample 24, zirconia was added as an "additive" in an amount corresponding to 0.4 wt% of the prepared metal powder mixture, and further mixed and crushed for 20 hours to prepare a slurry. For Samples 1 to 21 and 24 to 29, the prepared slurries were dried in a water bath to prepare respective dry powders, and the prepared dry powders were passed through a sieve with 100 μm openings to obtain granulated powders.
[0029] Among Samples 1 to 21 and 24 to 29, Samples 1 to 19, 21, 24 to 29 were produced by firing using the hot press method (HP) shown in the "Firing method" of the "Firing conditions" in Figures 2 and 3. In producing Samples 1 to 19, 21, 24 to 29, the obtained granulated powder was placed in a square hot press mold having a size of 30 mm x 30 mm so that the thickness of the sample was 20 mm, and firing was performed in a vacuum atmosphere under the "Temperature" and "Pressure" conditions of the "Firing conditions" in Figures 2 and 3.
[0030] Among Samples 1 to 21 and 24 to 29, Sample 20 was produced by sintering using the electric current sintering method (SPS) shown in the "sintering method" of the "sintering conditions" in Figure 3. In producing Sample 20, the obtained granulated powder was placed in a die for electric current sintering with a diameter of 10 mm so that the thickness of the sample would be 10 mm, and sintering was carried out in a vacuum atmosphere under conditions of a sintering temperature of 1900°C and a pressure of 70 MPa.
[0031] In producing samples 22 and 23, the raw materials used were metal oxides hafnium oxide (HfO2), zirconium oxide (ZrO2), titanium oxide (TiO2), tantalum oxide (Ta2O5), and niobium oxide (Nb2O5), as well as carbon (C). In producing samples 22 and 23, raw material powders having the average particle sizes shown below were used. Hafnium oxide powder: 2.0μm Zirconium oxide powder: 1.0μm Titanium oxide powder: 1.0 μm Tantalum oxide powder: 3.0μm Niobium oxide powder: 1.0μm Carbon powder: 5.0μm
[0032] Sample 22 was prepared with a composition of (HfZrTiTaNb) 0.6 C 0.4 The above-mentioned raw materials were weighed so that the composition of sample 23 was (HfZrTiTaNb) 0.4 C 0.6 The above-mentioned raw materials were weighed out so that the weight of the raw materials was 1600°C. In the preparation of samples 22 and 23, the weighed raw materials were mixed in a ball mill, and the mixed powder was heat-treated in a vacuum atmosphere at a temperature of 1600°C for 3 hours. Thereafter, the heat-treated powder was placed in a square hot press mold having a size of 30 mm x 30 mm so that the thickness of the sample was 20 mm, and sintered in a vacuum atmosphere at a sintering temperature of 1900°C and a pressure of 30 MPa.
[0033] FIG. 4 is a first diagram for explaining the characteristics of the ceramic sintered body sample. FIG. 5 is a second diagram for explaining the characteristics of the ceramic sintered body sample. FIG. 4 shows the number of elements corresponding to the first specific element and the characteristics obtained by various measurements for each of samples 1 to 16. FIG. 5 shows the number of elements corresponding to the first specific element and the characteristics obtained by various measurements for each of samples 17 to 29. Here, a method for measuring the characteristics of the samples shown in FIG. 4 and FIG. 5 will be described. In this evaluation test, a mirror-polished sample is used for measuring the characteristics. Note that, for each characteristic shown in FIG. 4 and FIG. 5, items that were not measured are marked with "-", and items whose measurement results are below the detection limit are marked with "ND".
[0034] The degree of single-phase formation was determined by identifying the crystal phase of the sample using an X-ray diffraction method with an X-ray diffraction device. Specifically, in the same manner as in the determination method for electrode chip 1, the crystal structure of the sample was analyzed using an X-ray diffraction method with CuKα1 ray, and the NaCl type structure was identified. <111> direction, <200> direction, <220> direction, <311> direction, <222> When there was only one peak from each of the directions at 30.0°-37.2°, 34.8°-43.1°, 50.2°-62.3°, 59.7°-74.4°, and 62.7°-78.5°, the sample was determined to be single-phase. For samples determined to be single-phase, the "relative density" was calculated using the theoretical density value calculated from the lattice constant obtained by Rietveld analysis, and the specific gravity and open porosity measured by the method according to JIS R1634.
[0035] "Atomic concentration difference" indicates the concentration difference between the first specific elements contained in the sample. "C concentration" indicates the concentration of carbon element contained in the sample. "Atomic concentration difference" and "C concentration" were obtained from the calculation results of the composition ratio in the crystal grains using energy dispersive X-ray spectroscopy.
[0036] "Zr concentration", "Y concentration", "Al concentration", and "Fe concentration" respectively indicate the concentrations of zirconium, yttrium, aluminum, and iron elements contained in the sample. In this evaluation test, an inductively coupled plasma optical emission spectrometer was used to confirm the presence or absence of yttrium or aluminum elements in the sample, and to measure "Zr concentration", "Y concentration", "Al concentration", and "Fe concentration".
[0037] "Oxidation resistance" was measured using a high-frequency plasma etching device. Specifically, the sample was etched by irradiating it with plasma at a high-frequency output of 100 W for 30 minutes in a reduced-pressure oxygen atmosphere in which the amount of oxygen was adjusted to a pressure of 30 Pa. The composition ratio of the sample after etching was calculated using energy dispersive X-ray spectroscopy, and the sample was evaluated based on the change in the amount of carbon and the amount of oxygen in the sample before and after the treatment. The evaluation criteria for the "oxidation resistance" of the sample are as follows: "◎": Carbon reduction of 2 at% or more, or oxygen increase of 4 at% or more "Good": Carbon reduction of 3 at% or more, or oxygen increase of 6 at% or more "△": Carbon reduction of 4 at% or more, or oxygen increase of 8 at% or more "X": Carbon reduction of 6 at% or more, or oxygen increase of 10 at% or more
[0038] "Wear resistance" indicates the degree of wear when a sample of the ceramic sintered body is used as an electrode for generating plasma. Specifically, the ceramic sintered body sample was processed to have a diameter of 1 mm and a length of 10 mm to prepare an evaluation electrode, and the anode was grounded and connected to a DC pulse power source. In an atmosphere containing a mixed gas of nitrogen and oxygen, plasma with a power of 300 W was discharged for 3 hours. After the discharge, the weight loss of the evaluation electrode was measured, and the wear amount of the evaluation electrode was calculated. In this evaluation test, the "wear amount" of samples 1 to 21 and 25 to 29 is a relative value when the wear amount of sample 20 is set to 100. In other words, the smaller the value of "wear resistance" shown in Figures 4 and 5, the less likely it is to wear.
[0039] It was clear that all of Samples 1 to 16 shown in Fig. 4 had five or six types of the first specific elements, and were single-phase. Samples 1 to 16 also had a relative density greater than 97% and a difference in atomic concentration less than 5 at%. Furthermore, Samples 1 to 16 had a carbon element concentration of 45 at% or more and 55 at% or less, and a yttrium element or aluminum element concentration of 3000 atppm or less.
[0040] All of Samples 1 to 16 contain zirconium element, and as shown in FIG. 4, the oxidation resistance is all rated as "◎" or "◯". Therefore, it is clear that they have better oxidation resistance than Samples 17 to 29 shown in FIG. 5 described later. Among Samples 1 to 16, when Samples 1 to 3 and 8 to 16, which have a relatively high concentration of zirconium element, are compared with Samples 4 to 7, which have a relatively low concentration of zirconium element, it is clear that Samples 1 to 3 and 8 to 16, which have a relatively high concentration of zirconium element, have further improved oxidation resistance.
[0041] Although samples 1 to 16 all contain iron element as an impurity, the concentration is 800 atppm or less. The wear resistance of samples 1 to 16 is relatively small, being all 40 or less, and it is clear that they are less susceptible to wear than samples 17 to 29 shown in Figure 5. Comparing samples 1 to 16, samples 1 to 3 and 8 to 16, which have relatively low iron element concentrations, with samples 4 to 7, which have relatively high iron element concentrations, it is clear that samples 1 to 3 and 8 to 16, which have relatively low iron element concentrations, have even improved wear resistance.
[0042] 5 are inferior to Samples 1 to 16 in both oxidation resistance and wear resistance. Here, the differences between Samples 17 to 29 and Samples 1 to 16 in terms of the respective properties will be described.
[0043] Sample 17 was fired at 1700°C (see FIG. 3), which is lower than the firing temperature of Samples 1 to 16, and was not made single-phase. Therefore, Sample 17 has low oxidation resistance, and when used as a plasma generating electrode that generates oxygen plasma, oxidation is likely to progress. Therefore, there is a risk that Sample 17 will have a short life as a plasma generating electrode.
[0044] During firing, Sample 18 was pressurized at 10 MPa (see FIG. 3), which was lower than the pressure applied to Samples 1 to 16, and therefore had more pores and a lower relative density than Samples 1 to 16. For this reason, Sample 18 is prone to heat generation due to electrical resistance, which may shorten its life as a plasma generating electrode.
[0045] Sample 19 uses only hafnium carbide as its "main raw material" (see Figure 3). Hafnium carbide oxidizes easily even at relatively low temperatures in an oxygen atmosphere, so its oxidation resistance was rated "X." Furthermore, hafnium carbide is a high-melting-point material that is difficult to sinter, and Sample 19, which was produced by hot pressing (see Figure 3), has many pores, a relatively small relative density, and is not densely formed. For this reason, Sample 19 has low wear resistance and is easily worn.
[0046] Like sample 19, sample 20 uses only hafnium carbide as the "main raw material", but is produced by "SPS (sintering process)" (see Figure 3). As a result, sample 20 is formed more densely than sample 19, and has a greater relative density, which results in improved wear resistance compared to sample 19. However, as mentioned above, hafnium carbide is easily oxidized, so the oxidation resistance was rated "x".
[0047] Sample 21 has the composition (Hf 0.1 Zr 0.225 Ti 0.225 Ta 0.225 Nb 0.225 )C. This results in a difference in atomic concentration of 6.5 at%, which is larger than the upper limit (5 at%) of the difference in atomic concentration of samples 1 to 16. If the difference in atomic concentration is larger than 5 at%, it becomes difficult to form a solid-solution single-phase structure, and therefore when used as a plasma generating electrode that generates oxygen plasma, oxidation is likely to proceed, and there is a risk of the life of the plasma generating electrode being shortened.
[0048] Sample 22 is formed using an oxide of the first specific element and carbon as raw materials, and has a composition of (HfZrTiTaNb) 0.6 C 0.4The carbon element concentration in sample 22 is 42.5 at%, which is lower than the lower limit (45 at%) of the carbon element concentration in samples 1 to 16. Therefore, in sample 22, the metal phase of the first specific element is likely to precipitate. Since the metal phase has a lower melting point than the carbide, it is likely to melt at the temperature at which it is used as a plasma generating electrode. Therefore, there is a risk that the life of the electrode as a plasma generating electrode will be shortened.
[0049] Sample 23 is formed using an oxide of the first specific element and carbon as raw materials, and has a composition of (HfZrTiTaNb) 0.4 C 0.6 The carbon element concentration of sample 23 is 57.2 at%, which is higher than the upper limit (55 at%) of the carbon element concentration of samples 1 to 16. This makes it easier for free carbon to precipitate, and when used as a plasma generating electrode, the discharge start voltage increases, causing the temperature of the plasma generating electrode itself to increase and make it more likely to melt. This may shorten the life of the plasma generating electrode.
[0050] Sample 24 is made using zirconia as an additive, instead of 3YSZ or Al2O3, and therefore does not contain yttrium or aluminum. If sample 24 does not contain yttrium or aluminum, the discharge start voltage will increase when used as a plasma generating electrode, making it more likely to melt and shortening the life of the plasma generating electrode.
[0051] Sample 25 has a composition of (TiNbV)C. That is, Sample 25 has three types of the first specific element, unlike Samples 1 to 16, which have five or six types. Also, Sample 25 has an iron element concentration of 1340 atppm%, which is higher than the upper limit (800 atppm) of the iron element concentration of Samples 1 to 16. If the iron element concentration is higher than 800 atppm, coarse iron-based particles are likely to precipitate. Iron-based particles have a low melting point and are likely to melt at the temperature at which they are used as a plasma generating electrode. Therefore, there is a risk that the life of the electrode as a plasma generating electrode will be shortened.
[0052] Sample 26 has a composition of (HfTiTaNbVWMo)C. That is, unlike Samples 1 to 16, which have five or six types of the first specific element, Sample 26 has seven types and is not single-phase. For this reason, like Sample 17, when Sample 26 is used as a plasma generating electrode that generates oxygen plasma, oxidation is likely to progress, and there is a risk of shortening the life of the plasma generating electrode.
[0053] Sample 27 has a composition of (HfZrTiTaNbVWMo)C. That is, unlike Samples 1 to 16, which have five or six types of the first specific element, Sample 27 has eight types of the first specific element and is not single-phase. For this reason, like Sample 26, when Sample 27 is used as a plasma generating electrode that generates oxygen plasma, oxidation is likely to progress, and there is a risk of shortening the life of the plasma generating electrode.
[0054] Sample 28 is added with 1.5 wt% of 3YSZ as an additive (see FIG. 3). As a result, the concentration of yttrium element in Sample 28 is 3958 atppm, which is higher than the upper limit of the concentration of yttrium element in Samples 1 to 16 (3000 atppm). Sample 29 is added with 0.3 wt% of aluminum oxide as an additive (see FIG. 3). As a result, the concentration of aluminum element in Sample 29 is 4013 atppm, which is higher than the upper limit of the concentration of aluminum element in Samples 1 to 16 (3000 atppm). When the concentration of yttrium element or the concentration of aluminum element is higher than 3000 atppm, yttrium or aluminum is likely to precipitate at the grain boundary of the ceramic sintered body, and the concentration of elements contained in the solid solution single-phase structure is likely to vary. Therefore, when used as a plasma generating electrode for generating oxygen plasma, oxidation is likely to proceed, and there is a risk that the life of the electrode as a plasma generating electrode will be shortened.
[0055] In sample 28, the zirconium element concentration is 18.08 at%, which is higher than the zirconium element concentration of 15 at% in samples 1 to 16. In the ceramic sintered body, if the zirconium element concentration exceeds 15 at%, a multi-phase structure containing zirconium is generated, and the concentration distribution of the first specific element in the grains of the single-phase structure of the first specific element becomes non-uniform. As a result, when used as a plasma generation electrode that generates oxygen plasma, oxidation is likely to proceed, and there is a risk of shortening the life of the plasma generation electrode.
[0056] In cutting machines and surface treatment devices using plasma, high melting point metal materials such as hafnium, zirconium, and tungsten may be used as the plasma generating electrode. However, the plasma generating electrode is easily worn out due to heat generation of the plasma generating electrode itself caused by high plasma arc current and oxidation caused by plasma gas species such as oxygen, and the life of the plasma generating electrode may be relatively short. Therefore, hafnium carbide, which has an even higher melting point, may be used as the material for the plasma generating electrode. However, as explained in the above samples 19 and 20, hafnium carbide is easily oxidized even at relatively low temperatures in an oxygen atmosphere, so there was concern about a decrease in life due to oxidation in a plasma atmosphere containing oxygen. In addition, hafnium carbide is difficult to sinter, so a large voltage is required to obtain a sintered body with a large size, and a dense sintered body could only be obtained by the electric current sintering method, which is prone to increasing equipment costs and manufacturing costs. In addition, it is difficult to sinter uniformly with the electric current sintering method, and the degree of freedom in shape is low.
[0057] The ceramic sintered body provided in the electrode tip 1 of this embodiment contains titanium, zirconium, niobium, hafnium, and tantalum as the first specific elements, and yttrium and carbon as the second specific elements. The ceramic sintered body forms a solid solution in which five types of the first specific elements are made into a single phase, so that oxidation is suppressed, for example, even in an atmosphere in which oxygen plasma is present. In addition, since the first specific elements contain elements with a lower melting point than hafnium carbide, for example, a dense ceramic sintered body can be produced by a sintering method such as hot pressing. As a result, the ceramic sintered body provided in the electrode tip 1 of this embodiment can have a complex shape while reducing the device cost and manufacturing cost. In addition, the electrode tip 1 can have a longer life than hafnium and hafnium carbide.
[0058] The ceramic sintered body included in the electrode tip 1 of the present embodiment described above has a single-phase structure in which the first specific elements consisting of five or six elements selected from titanium, vanadium, zirconium, niobium, molybdenum, hafnium, tantalum, and tungsten are dissolved in solid solution. This can improve the oxidation resistance of the ceramic sintered body included in the electrode tip 1.
[0059] In addition, the ceramic sintered body included in the electrode tip 1 of this embodiment contains zirconium as the first specific element. This increases the distortion of the crystal lattice in the single-phase structure in which the first specific element is dissolved. Therefore, the ceramic sintered body included in the electrode tip 1 is less susceptible to oxidation, and the oxidation resistance of the ceramic sintered body can be further improved.
[0060] In addition, the ceramic sintered body of the electrode tip 1 of this embodiment has an iron element concentration of 800 atppm or less, so that the precipitation of coarse iron-based particles is suppressed. This suppresses melting of the ceramic sintered body due to a rise in temperature, so that the weight loss of the ceramic sintered body due to use can be suppressed. Therefore, the life of the electrode tip 1 can be extended.
[0061] The electrode tip 1 of this embodiment includes a ceramic sintered body having a single-phase structure in which a first specific element consisting of five or six elements selected from titanium, vanadium, zirconium, niobium, molybdenum, hafnium, tantalum, and tungsten is dissolved in a solid solution. This improves the oxidation resistance of the electrode tip 1, thereby extending the life of the electrode for generating plasma.
[0062] In addition, the electrode tip 1 of this embodiment is manufactured by hot pressing, which allows the electrode tip 1 to have a complex shape while reducing the device cost and manufacturing cost compared to a plasma generation electrode made of hafnium or hafnium carbide manufactured by electric current sintering.
[0063] <Modifications of this embodiment> The present invention is not limited to the above-described embodiment, and can be embodied in various forms without departing from the spirit and scope of the invention. For example, the following modifications are also possible.
[0064] [Variation 1] In the above embodiment, the ceramic sintered body of the electrode tip 1 contains five types of elements, titanium, zirconium, niobium, hafnium, and tantalum, as the first specific element. It is sufficient that the ceramic sintered body contains five or six types of elements among titanium, vanadium, zirconium, niobium, molybdenum, hafnium, tantalum, and tungsten.
[0065] [Variation 2] In the above embodiment, the electrode tip 1 includes a combination of titanium, zirconium, hafnium, and tantalum as the first specific element. However, the preferred combination of the first specific element is not limited to this. A combination of zirconium, hafnium, and tantalum is also preferred, and the combination of hafnium and tantalum can further improve the oxidation resistance of the electrode tip 1.
[0066] [Variation 3] In the above embodiment, the electrode tip 1 has a zirconium element concentration of 8.43 at%. However, the first specific element contained in the electrode tip 1 to improve the oxidation resistance of the electrode tip 1 is not limited to zirconium. By containing hafnium, tantalum, titanium, etc. instead of zirconium, the oxidation resistance of the electrode tip 1 can be improved.
[0067] [Variation 4] In the above embodiment, the iron element (Fe) contained in the ceramic sintered body of the electrode chip 1 is 800 atppm or less. The iron element may be greater than 800 atppm, but a low iron element concentration is preferable because a high iron element concentration shortens the lifespan of the precipitated iron-based particles by melting them. The iron element concentration may be less than the measurement limit when measured by an inductively coupled plasma optical emission spectrometry device.
[0068] [Variation 5] The ceramic sintered body of the above embodiment is provided in the electrode tip 1. The technical field to which the ceramic sintered body is applied is not limited to this. The ceramic sintered body may be used in technical fields requiring oxidation resistance and wear resistance.
[0069] Although the present aspect has been described above based on the embodiment and modified examples, the above-mentioned embodiment of the aspect is intended to facilitate understanding of the present aspect and does not limit the present aspect. The present aspect may be modified or improved without departing from the spirit and scope of the claims, and equivalents are included in the present aspect. Furthermore, if a technical feature is not described as essential in this specification, it may be deleted as appropriate.
[0070] <Application example 1> A ceramic sintered body, a first specific element consisting of five or six elements selected from titanium (Ti), vanadium (V), zirconium (Zr), niobium (Nb), molybdenum (Mo), hafnium (Hf), tantalum (Ta), and tungsten (W); A second specific element consisting of one element selected from yttrium (Y) and aluminum (Al); Carbon element (C), the total content of the first specific element, the second specific element, and carbon element contained in the ceramic sintered body is 98 at % or more; The second specific element contained in the ceramic sintered body is 3000 atppm or less, The carbon content of the ceramic sintered body is 45 at % or more and 55 at % or less, The first specific element has a single-phase structure in which the first specific element is dissolved. A ceramic sintered body comprising: <Application example 2> The ceramic sintered body according to Application Example 1, The first specific element includes zirconium. A ceramic sintered body comprising: <Application example 3> The ceramic sintered body according to Application Example 1 or Application Example 2, The iron element (Fe) contained in the ceramic sintered body is 800 atppm or less. A ceramic sintered body comprising: <Application Example 4> A plasma generating electrode, The ceramic sintered body according to any one of Application Examples 1 to 3 is provided. Electrode for generating plasma. [Explanation of symbols]
[0071] 1...Electrode tip (sintered ceramics) 10...Plasma generating electrode
Claims
1. A ceramic sintered body, a first specific element consisting of five or six elements selected from titanium (Ti), vanadium (V), zirconium (Zr), niobium (Nb), molybdenum (Mo), hafnium (Hf), tantalum (Ta), and tungsten (W); a second specific element consisting of one element selected from yttrium (Y) and aluminum (Al); A carbon element (C), the total content of the first specific element, the second specific element, and carbon element contained in the ceramic sintered body is 98 at% or more; The second specific element contained in the ceramic sintered body is 3000 atppm or less, The carbon content of the ceramic sintered body is 45 at % or more and 55 at % or less, The first specific element has a single-phase structure in which the first specific element is dissolved. A ceramic sintered body comprising:
2. The ceramic sintered body according to claim 1, The first specific element includes zirconium. A ceramic sintered body comprising:
3. The ceramic sintered body according to claim 1 or 2, The iron element (Fe) contained in the ceramic sintered body is 800 atppm or less. A ceramic sintered body comprising:
4. A plasma generating electrode, The ceramic sintered body according to claim 1 or 2 is provided. Electrode for generating plasma.
Citation Information
Patent Citations
Method for preparing compact (HfZrTaNbTi) C high-entropy ceramic sintered body through normal-pressure sintering
CN111410536A
Easy-to-sinter wear-resistant friction-reducing high-entropy ceramic material and preparation method thereof
CN114031406A
Production of composite material and raw material composition
JP1990212360A
Rotary tool and sintered compact
JP2011062743A
Hafnium carbide powder for plasma electrode, manufacturing method therefor, hafnium carbide sintered body and plasma electrode
JP2019073426A
Cited By
Ceramic sintered body, plasma-generating electrode, and heat-resistant member
WO2026204375A1